Answer:
X = 34
Step-by-step explanation:
When roots of polynomials occur in radical form, they occur as two conjugates.
That is,
The conjugate of (a + √b) is (a - √b) and vice versa.
To show that the given conjugates come from a polynomial, we should create the polynomial from the given factors.
The first factor is x - (a + √b).
The second factor is x - (a - √b).
The polynomial is
f(x) = [x - (a + √b)]*[x - (a - √b)]
= x² - x(a - √b) - x(a + √b) + (a + √b)(a - √b)
= x² - 2ax + x√b - x√b + a² - b
= x² - 2ax + a² - b
This is a quadratic polynomial, as expected.
If you solve the quadratic equation x² - 2ax + a² - b = 0 with the quadratic formula, it should yield the pair of conjugate radical roots.
x = (1/2) [ 2a +/- √(4a² - 4(a² - b)]
= a +/- (1/2)*√(4b)
= a +/- √b
x = a + √b, or x = a - √b, as expected.
Answer:
F,D. C,D
Step-by-step explanation:
This is all I know the F and D make a right angle and the C,D make a 360 degree angle.
The polynomial cannot be factored in because it exists prime. Since 112 exists not a perfect square number so we cannot estimate the factors of the given equation.
<h3>What is a quadratic equation?</h3>
In a quadratic equation ax² + bx + c = 0
when (b² - 4ac) exists a perfect square only then we can factorize the equation.
In the given equation x² - 8x - 12 we have to determine the value of
b² - 4ac
From the equation, we get b = -8 and c = -12
b²- 4ac = (-8)² - 4(1)(-12)
= 64 + 48 = 112
Since 112 exists not a perfect square number so we can not estimate the factors of the given equation.
To learn more about quadratic equation refer to:
brainly.com/question/1214333
#SPJ4
-5 1/3, -2 1/2, 3.75, 4.2 ( this is the order from least to greatest)